The bedrock topography of Gries- and Findelengletscher - N. Feiger; N. Feiger; M. Huss; M. Huss; S. Leinss; L. Sold; D. Farinotti; D. Farinotti (Geographica Helvetica, 2018)
Knowledge of the ice thickness distribution of glaciers is important for glaciological and hydrological applications. In this contribution, we present two updated bedrock topographies and ice thickness distributions for Gries- and Findelengletscher, Switzerland. The results are based on ground-penetrating radar (GPR) measurements collected in spring 2015 and already-existing data. The GPR data are analysed using ReflexW software and interpolated by using the ice thickness estimation method (ITEM). ITEM calculates the thickness distribution by using principles of ice flow dynamics and characteristics of the glacier surface. We show that using such a technique has a significance advantage compared to a direct interpolation of the measurements, especially for glacier areas that are sparsely covered by GPR data. The uncertainties deriving from both the interpretation of the GPR signal and the spatial interpolation through ITEM are quantified separately, showing that, in our case, GPR signal interpretation is a major source of uncertainty. The results show a total glacier volume of 0.28 ± 0.06 and 1.00 ± 0.34 km3 for Gries- and Findelengletscher, respectively, with corresponding average ice thicknesses of 56.8 ± 12.7 and 56.3 ± 19.6 m.